Effect of high- and low-caloric mixed liquid meals on intestinal gas dynamics - Harder, Hermann; Hernando-Harder, Ana C.; Franke, Andreas; Krammer, H.; Singer, Manfred V. (Digestive diseases and sciences, 2006)
High-caloric meals can evoke postprandial abdominal complaints involving disturbances in intestinal gas balance. We aimed to determine the influence of the caloric content of meals on intestinal gas dynamics. Eight healthy subjects (five women, three men; age range, 25-43 years) underwent paired studies with low (1 kcal/min)- and high (3 kcal/min)-caloric meal infusion 35% fat, (45% carbohydrate, 20% protein) into the duodenum in random order and proximal jejunal gas infusion. Gas evacuation, perception, and abdominal girth were assessed. The low-caloric meal caused neither gas retention (-7 ± 58 ml) nor girth changes (0 ± 0 mm). In contrast, the high-caloric meal led to significant gas retention (705 ± 56 ml) and increased abdominal perimeter (7 ± 1 mm; P < 0.001 vs. the low-caloric meal for both). Thus, a high caloric load of nutrients arriving at the duodenum modulates both intestinal gas transit and abdominal perimeter.